Role of Winds in Interrupting the Formation of Coastal Hypoxia - Wang, Kuo; Yao, Juan; Wang, Juying; Liu, Hongbin; Yin, Kedong (Frontiers in Marine Science, 2022)
Enrichment of nutrients is believed to lead to coastal hypoxia which have become a seasonal phenomenon over large river estuarine areas such as the Mississippi River-Northern Gulf of Mexico and Changjiang-East China Sea. A similar nutrient enrichment process exists in the Pearl River. However, hypoxia occurs only as episodic events over a relatively small area. We hypothesize that frequent wind events play the interruptive mechanism in preventing the seasonal formation of bottom hypoxia. We used 29 years’ time series data of dissolved oxygen (DO) and winds in the Hong Kong coastal waters to test the hypothesis. Our results show that bottom DO at 3 stations in southern waters of Hong Kong occasionally drops below the hypoxic level (2 mg/L), lasting only for less than one month in summer. Episodic hypoxia events appear to occur more frequently in recent years, but bottom DO does not show a significantly decreasing trend. The wind speed of 6 m/s appears to be a threshold, above which a wind event could destroy water column stratification and interrupt the formation of low-oxygen (DO <3 mg/L) water mass. The wind events above the threshold occur 14.3 times in June, 14.2 times in July and 10.0 times in August during 1990-2018. This explains why episodic events of hypoxia hardly occur in June and July, and only occasionally in August. The frequency of such the above-threshold events appears to show a decreasing trend during 1990-2018, which coincides with an increasing occurrences of episodic hypoxia events in recent years